Temperature during conidiation affects stress tolerance, pigmentation, and trypacidin accumulation in the conidia of the airborne pathogen Aspergillus fumigatus. - Daisuke Hagiwara; Kanae Sakai; Satoshi Suzuki; Myco Umemura; Toshihiko Nogawa; Naoki Kato; Hiroyuki Osada; Akira Watanabe; Susumu Kawamoto; Tohru Gonoi; Katsuhiko Kamei (PLoS ONE)
Asexual spores (conidia) are reproductive structures that play a crucial role in fungal distribution and survival. As fungal conidia are, in most cases, etiological agents of plant diseases and fungal lung disease, their stress resistance and interaction with their hosts have drawn increasing attention. In the present study, we investigated whether environmental temperature during conidiation affects the stress tolerance of the conidia of the human pathogenic fungus Aspergillus fumigatus. Conidia from a 25°C culture showed a lower tolerance to heat (60°C) and oxidative (H2O2) stresses and a marked resistance to ultraviolet radiation exposure, compared with those produced at 37 and 45°C. The accumulation of trehalose was lower in the conidia from the 25°C culture. Furthermore, the conidia from the 25°C culture showed darker pigmentation and increased transcripts of dihydroxynaphthalene (DHN)-melanin biosynthesis-related genes (i.e., pksP, arp1, and arp2). An RNA-sequencing analysis revealed that the transcription level of the trypacidin (tpc) gene cluster, which contains 13 genes, was sharply and coordinately activated in the conidia from the 25°C culture. Accordingly, trypacidin was abundant in the conidia from the 25°C culture, whereas there was little trypacidin in the conidia from the 37°C culture. Taken together, these data show that the environmental temperature during conidiation affects conidial properties such as stress tolerance, pigmentation, and mycotoxin accumulation. To enhance our knowledge, we further explored the temperature-dependent production of DHN-melanin and trypacidin in clinical A. fumigatus isolates. Some of the isolates showed temperature-independent production of DHN-melanin and/or trypacidin, indicating that the conidia-associated secondary metabolisms differed among the isolates.